2021
DOI: 10.1111/nph.17802
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of responses of C3 plants to atmospheric CO2: dose–response curves for 85 traits ranging from the molecular to the whole‐plant level

Abstract: Generalised dose-response curves are essential to understand how plants acclimate to atmospheric CO 2 . We carried out a meta-analysis of 630 experiments in which C 3 plants were experimentally grown at different [CO 2 ] under relatively benign conditions, and derived dose-response curves for 85 phenotypic traits. These curves were characterised by form, plasticity, consistency and reliability. Considered over a range of 200-1200 µmol mol À1 CO 2 , some traits more than doubled (e.g. areabased photosynthesis; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 766 publications
(135 reference statements)
3
69
0
Order By: Relevance
“…5e, PI = 1.3), be it with a low consistency. This mirrors the effect of [CO 2 ], where leaf N/P decreases with increasing CO 2 levels (Poorter et al 2022), also with relatively low consistency. It would be interesting to test whether the opposing effects of light and [CO 2 ] on the transpiration rate differentially affects mass flow around the roots, thereby affecting the uptake of nitrate more than of phosphorous compounds.…”
Section: Dose-response Curves For 12 Additional Traitssupporting
confidence: 52%
See 2 more Smart Citations
“…5e, PI = 1.3), be it with a low consistency. This mirrors the effect of [CO 2 ], where leaf N/P decreases with increasing CO 2 levels (Poorter et al 2022), also with relatively low consistency. It would be interesting to test whether the opposing effects of light and [CO 2 ] on the transpiration rate differentially affects mass flow around the roots, thereby affecting the uptake of nitrate more than of phosphorous compounds.…”
Section: Dose-response Curves For 12 Additional Traitssupporting
confidence: 52%
“…Enzymes are major engines of cell metabolism, and the different chemical compounds produced may reflect the physiological status plants are in. So far, we have only been able to include Rubisco amount or activity as an important enzymatic factor in C-fixation, and chlorophyll, xanthophylls and other carotenoids, and soluble phenolics as relevant groups of specific metabolic compounds (Poorter et al 2019(Poorter et al , 2022. However, there is a wide range of enzymes and compounds that could be instructive for the physiological status of plants.…”
Section: Dose-response Curves For Gene Expression Enzyme Activities A...mentioning
confidence: 99%
See 1 more Smart Citation
“…This gave b HS = 1 × 10 −5 mol cm −3 pH −1 . We took a typical value for CO 2 pressure in the soil air of 0.004 atm (Poorter et al, 2021).…”
Section: Soil Parametersmentioning
confidence: 99%
“…Yu and Korner [ 11 ] and Kizildeniz et al [ 12 ] found no effect of elevated CO 2 on leaf size in tomato and grape leaves, respectively. A recent meta-analysis of responses of C 3 plants indicated an average slight linear increase in leaf size with increasing CO 2 [ 13 ], but with relatively low consistency. Ultimately, leaf size is determined by the combination of cell numbers and cell size.…”
Section: Introductionmentioning
confidence: 99%